Electron Microscopy investigation of Sb2-xBixTe3hexagonal crystal structure growth prepared from sol-gel method - Suparat Tongpeng (2018)
© 2015 Elsevier B.V. Sb - Bi - Te ternary compounds, with ZT values (unitless figure of merit for semiconductor materials) as high as 1.28, have long been known as the best thermoelectric materials for use in thermoelectric cooling and power generation operated near room temperature. In this research, p-type Sb2-xBixTe3(x = 0, 0.2, 0.4, 0.6, 0.8, and 1.0) compounds were synthesized by sol-gel method using bismuth (III) acetate, antimony (III) acetate and tellurium dioxide as precursors. The mole ratio of metal precursor: solvent: organic solvent was 1:60:4. The obtained gels of Sb2-xBixTe3were annealed to complete the synthesis at 773 K for 2 h under nitrogen atmosphere. Sb2Te3, Sb1.6Bi0.4Te3, and SbBiTe3compounds were observed by X-ray Diffraction (XRD) as main phases in samples with x = 0-0.2, 0.4-0.6, and 0.8-1.0, respectively. An increase in the lattice parameter a suggested an expansion of unit cells, due to the substitution of Bi in Sb crystallographic positions. The morphology, as revealed by Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) images, is one of aligned hexagonal nanosheets, while the Selected Area Diffraction (SAD) patterns matched well with the phases characterized by XRD.